Hadith #2600 - Sunan Abi Dawud - Abu Ja'far al-Khutami, 'Umayr bin Yazid عمير بن يزيد أبو جعفر الخطمي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Salama حماد بن سلمة; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yahya bin Ishaq يحيى بن إسحاق (Sunan Abi Dawud)
Qaza’ah said Ibn ‘Umar told me “Come, I see off you as the Apostle of Allaah(ﷺ) saw me off. I entrust to Allaah your religion what you are responsible for and your final deeds.”
Grade: Sahih

Hadith #3891 - Sunan Abi Dawud - Abu al-Darda; al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
I had a pain which was about to destroy me. So the Prophet (ﷺ) said : Wipe it with your right hand seven times and say : “I seek refuge in the dominance of Allah, and His might from the evil of what I find.” Then I did it. Allah removed (the pain) that I had, and I kept on suggesting it to my family and to others.
Grade: Sahih

Hadith #5062 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
Fatimah complained to the Prophet (May peace be upon him) of the effect of the grinding stone on her hand. Then some slaves (prisoners of war) were brought to him. So she went to him to ask for (one of) them, but she did not find him. She mentioned the matter to ‘A’ishah. When the prophet (May peace be upon him) came, she informed him. He (the prophet) visited us (Ali) when we had gone to bed, and when we were about to get up, he said: stay where you are. He then came and sat down between us
Grade: Sahih

Hadith #5087 - Sunan Abi Dawud - Aban bin 'Uthman أبان بن عثمان بن عفان; Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Uthman ibn 'Affaan (Sunan Abi Dawud)
If anyone says in the morning: “O Allah! whatever oath I take, whatever word I speak, and whatever vow I take, Thine will precedes all that: whatever Thou willeth, occurs, and whatever Thou dost not will, dost not occur. O Allah! pardon me and disregard me for it. O Allah! whomsoever Thou sendest thine blessing, to him my blessing is due, and whomsoever thou cursest, to him my curse is due, ” exemption from it will be granted to him that day.
Grade: Da'if

Hadith #66 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Ubaidullah bin 'Abdur Rahman bin Rafa' عبيد الله بن عبد الرحمن بن رافع (Jami' al-Tirmidhi)
“It was said, ‘O Allah’s Messenger! Shall we use the water of Buda’ah well to perform ablution while it is a well in which menstruation rags, flesh of dogs and the putrid are dumped?” Allah’s Messenger said: ‘Indeed water is pure, nothing makes it impure.'”
Grade:

Hadith #799 - Jami' al-Tirmidhi - Abdullah ibn Ja'far; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
“I went to Anas bin Malik during Ramadan and he was about to travel. His mount was prepared for him, and he put on his traveling clothes, then he called for some food to eat, and I said to him: ‘Is it Sunnah?’ He said: ‘It is Sunnah.’ Then he rode.”
Grade:

Hadith #800 - Jami' al-Tirmidhi - Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Sa'id bin Abi Maryam سعيد بن أبي مريم; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
“I went to Anas bin Malik during Ramadan” and he mentioned a similar narration (as no. 799).
Grade:

Hadith #1120 - Jami' al-Tirmidhi - ibn Abbas; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Musa bin 'Ubaida bin Nashayt موسى بن عبيدة بن نشيط; Sufyan bin 'Uqba al-Swa'iy سفيان بن عقبة السوائي الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Jami' al-Tirmidhi)
“The Messenger of Allah cursed the Muhill and the one the Muhallal was done for.”
Grade:

Hadith #2590 - Jami' al-Tirmidhi - Ali ibn Abi Talib; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Jami' al-Tirmidhi)
“The Fire was kindled for one thousand years until it reddened, then it was kindled for one thousand years until it whitened, then it was kindled for one thousand years until it became blackened, so it is dark black.”
Grade:

Hadith #2593 - Jami' al-Tirmidhi - Ali ibn Abi Talib; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Jami' al-Tirmidhi)
“Allah will say: ‘Remove from the Fire whoever remembered Me one day, or feared Me while in a state of sinning.”
Grade:

Hadith #3074 - Jami' al-Tirmidhi - Abu Bakr al-Hanfi عبد الكبير بن عبد المجيد- أبو بكر الحنفي; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Ayoub bin Musa bin 'Amr bin Sa'id أيوب بن موسى بن عمرو; ibn Mas'ud; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي (Jami' al-Tirmidhi)
“Hammad bin Salamah narrated to us, from Thabit, from Anas, that the Prophet (ﷺ) recited this Ayah: So when his Lord appeared to the mountain, He made it collapse to dust (7:143) – Hammad said: “Like this.” Sulaiman held his thumb over the tip of his finger on the right hand (so that only the tip of one finger was protruding) – and he said: “So the mountain fainted. ‘And Musa fell down unconscious.'”
Grade:

Hadith #3545 - Jami' al-Tirmidhi - al-Hakam bin 'Utayba الحكم بن عتيبة; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zayd bin Arqam (Jami' al-Tirmidhi)
“The stingy person is the one before whom I am mentioned, and he does not send Salat upon me.”
Grade:

Hadith #145 - Sunan Ibn Majah - Abu Sbrh أبو سبرة; al-'Abbas ibn 'Abd al-Muttalib; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Muhammad bin Tryf bin Khlyf محمد بن طريف بن خليف; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
“I saw the Messenger of Allah performing ablution, taking one handful (of water) at a time.'”
Grade:

Hadith #1012 - Sunan Ibn Majah - ibn Abbas; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Ibn Majah)
It was narrated from ‘Amr bin Shu’aib, from his father, from his grandfather, that the Prophet (ﷺ) said the Takbir seven times and five times in the ‘Eid prayer.
Grade:

Hadith #1237 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Salah bin Hasaan al-Nadri صالح بن حسان النضري (Sunan Ibn Majah)
“I prayed with ‘Abdullah bin Abi Awfa Al-Aslami, the Companion of the Messenger of Allah (ﷺ), offering the funeral prayer for a daughter of his. He said Takbir over her four times, and he paused for a while after the fourth. I heard the people saying Subhan- Allah to him throughout the rows. Then he said the Salam and said: ‘Did you think that I was going to say a fifth Takbir?’ They said: ‘We were afraid of that.’ He said: ‘I was not going to do that, but the Messenger of Allah
Grade:

Hadith #2671 - Sunan Ibn Majah - Abdul 'Aziz bin Abi Hazim عبد العزيز بن أبي حازم; Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Abu Hurairah; al-Mughira bin 'Abdur Rahman - Qusayy المغيرة بن عبد الرحمن بن عبد الله - قصي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Musa bin Yasar al-Urdani موسى بن يسار الأردني; Najih bin 'Abdur Rahman نجيح بن عبد الرحمن السندي; Suhayl bin Abi Salah سهيل بن أبي صالح; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) entered upon me when I was unwell. He said: ‘Do you intend to perform Hajj this year?’ I said: ‘I am sick, O Messenger of Allah.’ He said: ‘Go for Hajj and say: “I will exit Ihram from the point where I am prevented.’”
Grade:

Hadith #3196 - Sunan Ibn Majah - Abdullah bin Nafi' al-Sa'agh عبد الله بن نافع الصائغ المخزومي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Ka'b bin 'Ajra al-Salmi, al-Ansari; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Usamah ibn Zayd (Sunan Ibn Majah)
“I brought a son of mine to the Prophet (ﷺ), and I had pressed on an area of his throat due to tonsillitis. He said: ‘Why do you poke your children with this pressing?’ You should use this aloeswood, for in it there are seven cures. It should be inhaled for pustules in the throat, and given in the side of the mouth for pleurisy.” (Another chain) from Umm Qais bint Mihsan, from the Prophet (ﷺ) with similar wording.
Grade:

Hadith #3864 - Sunan Ibn Majah - ibn Abbas; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Salah bin Hasaan al-Nadri صالح بن حسان النضري (Sunan Ibn Majah)
“This Verse was revealed concerning us six: Myself, Ibn Mas’ud, Suhaib, ‘Ammar, Miqdad and Bilal. The Quraish said to the Messenger of Allah (ﷺ): ‘We do not want to join them, send them away.’ Thoughts of that entered the heart of the Messenger of Allah (ﷺ) as much as Allah willed, then Allah revealed: “And turn not away those who invoke their Lord, morning and afternoon seeking His Face. You are accountable for them in nothing, and they are accountable for you in nothing, that y
Grade: